1999
DOI: 10.1093/ps/78.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary roxarsone supplementation, lighting program, and season on the incidence of leg abnormalities in broiler chickens

Abstract: Two 4 x 2 factorial experiments were designed to test the effects of four diets, differing in anticoccidial programs and roxarsone (3-nitro-4-hydroxyphenylarsonic acid) content, and two lighting programs on the incidence of leg abnormalities in 56-d-old male and female broiler chickens. The four diets were: A) basal diet + salinomycin (60.0 g/ton); B) basal diet + salinomycin (60.0 g/ton) + roxarsone (45.4 g/ton); C) basal diet + roxarsone (45.4 g/ton) + live coccidial vaccine; and D) basal diet + live coccidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…Despite examining a fuller range of husbandry and management practices than previous surveys, we did not identify many novel or previously unreported risks. An effect of season has been noted before in the US, where a higher percentage of leg abnormalities was reported in the summer [25] . The strong genotype effect that we found, confirms the important genetic component to leg disorders, and many of the husbandry effects detected most likely alter levels of leg disorder through direct or indirect effects on growth rate.…”
Section: Discussionsupporting
confidence: 58%
“…Despite examining a fuller range of husbandry and management practices than previous surveys, we did not identify many novel or previously unreported risks. An effect of season has been noted before in the US, where a higher percentage of leg abnormalities was reported in the summer [25] . The strong genotype effect that we found, confirms the important genetic component to leg disorders, and many of the husbandry effects detected most likely alter levels of leg disorder through direct or indirect effects on growth rate.…”
Section: Discussionsupporting
confidence: 58%
“…Body weight gain in chicks exposed to intermittent lighting was greater than that exposed to either continuous or constant lighting program, the differences in this respect, were significant (P<0.01) during 4-7 and significant (P<0.05) during 1-7 between intermittent and constant lighting programs (Table 2). This finding agree with the results of Al-Homidan (1994), Renden et al (1996), Laster et al, (1999) and Othani and Lesson (2000). El-Neney (2003) showed that under intermittent light birds had significantly heavier body weight than those of continuous light and constant light.…”
Section: Live Body Weight and Weight Gainsupporting
confidence: 93%
“…Petek et al (2005) have reported similar results. Contrary some researchers (Wilson et al, 1984;Laster et al, 1999;Ingram et al, 2000) showed that IL had significantly fewer and less severe skeletal diseases. This may be explained due to the positive correlation between TD and body weight (Su et al, 1999) and also may be due to the different slaughter ages.…”
Section: Discussionmentioning
confidence: 79%